IMPROVING THE DESIGN OF PRIMARY COTTON CLEANING MACHINES TO ENHANCE ROVING QUALITY - Matchanova Gulruh Xayitmatovna (Innovate Conferences, 2025)
The efficiency of primary cotton fiber cleaning significantly impacts the quality of the final textile product. This study examines the effect of modifying the second drum’s teeth configuration in the CL-P cleaning machine to optimize roving quality. Experimental analysis using the Uster AFIS PRO-2 device revealed improvements in short fiber content, dust removal, and foreign matter reduction. The modified CL-P machine demonstrated enhanced cleaning efficiency, aligning with Uster 25% standards. However, minor adjustments are needed to optimize neps content. Implementing these improvements in industrial applications can enhance fiber processing efficiency and product quality.